1994
DOI: 10.1007/bf00947964
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 deoxyglucose uptake in sarcoidosis measured with positron emission tomography

Abstract: Regional pulmonary glucose metabolism (MRglu; mumol h-1 g-1), extravascular lung density (D(EV); g cm-3) and vascular volume (VB; ml cm-3) were measured in a single midthoracic transaxial slice (approximately 2 cm thick) using position emission tomography (PET) in seven patients with histologically proven sarcoidosis. The measurements were repeated 1-7 months later after steroid therapy (in two cases, no treatment) in order to assess MRglu as an index of inflammation and relate it to routine pulmonary function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(57 citation statements)
references
References 25 publications
2
51
0
4
Order By: Relevance
“…[11] 18 FDG accumulating within the sarcoid granuloma show the classical presence of a rich infiltrate of lymphocytes and macrophages [12,13] even if 18 FDG-PET/CT is not specific for sarcoidosis, and other pathological benign thoracic lesions showing 18 FDG uptake include infection, inflammation, granulomatosis and sarcoidosis. [14,15] The appearance of lymph nodes at thoracic computer tomography is quite characteristic of sarcoidosis and in our case, multiple enlarged lymph nodes at the mediastinum were found, the majority being confluent which was compatible with sarcoidosis, but some lymph nodes were colliquate and this was not typcal of the disease. Thus, the findings of the…”
Section: Discussionsupporting
confidence: 50%
“…[11] 18 FDG accumulating within the sarcoid granuloma show the classical presence of a rich infiltrate of lymphocytes and macrophages [12,13] even if 18 FDG-PET/CT is not specific for sarcoidosis, and other pathological benign thoracic lesions showing 18 FDG uptake include infection, inflammation, granulomatosis and sarcoidosis. [14,15] The appearance of lymph nodes at thoracic computer tomography is quite characteristic of sarcoidosis and in our case, multiple enlarged lymph nodes at the mediastinum were found, the majority being confluent which was compatible with sarcoidosis, but some lymph nodes were colliquate and this was not typcal of the disease. Thus, the findings of the…”
Section: Discussionsupporting
confidence: 50%
“…So far, sarcoid activity has been demonstrated by FDG-PET in the hilar and mediastinal lymph nodes, in the lungs and in the bones [2, 3, 4, 5, 6]. In the individual patient, FDG-PET can probably be employed to evaluate the extent of sarcoid organ involvement, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, FDG-PET can also be used as a marker of inflammation, e.g. to visualise inflammatory granulomatous disorders such as sarcoidosis [2, 3, 4, 5, 6]. The objective of the present case study was to study changes in FDG-PET in pulmonary sarcoidosis prior to and during treatment with inhaled as well as oral corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic imaging with 2-(18F)-fluoro-2-deoxy-D-glucose positron emission tomography (PET) is being used more and more to differentiate benign from malignant focal lesions and it has been shown to be more efficious than conventional chest CT. Howewer, fluorodeoxyglucose (FDG) is not a cancer-specific agent, and false positive findings in benign diseases have been reported in active inflammation or infection, causing false-positive results. Active granulomatous conditions with agregation of inflammatory cells in sarcoidosis results in accumulation of FDG and it has been suggested that the intensity of FDG uptake may reflect disease activity (Brudin et al, 1994). A retrospective study was conducted by Chowdhury et al to evaluate the prevalence of sarcoid-like reaction to malignancy detected using integrated 18 FDG PET/CT in patients undergoing staging or restaging of solid-organ malignancy (Chowdhury et al, 2009).…”
Section: Diagnostic Strategymentioning
confidence: 99%